An Estimate of the Prevalence of COPD in Africa: A Systematic Analysis. (1st February 2015) - Adeloye, Davies; Basquill, Catriona; Papana, Angeliki; Chan, Kit Yee; Rudan, Igor; Campbell, Harry
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is among the leading causes of death globally, accounting for about 3 million deaths worldwide in 2011. We aimed to estimate the prevalence of COPD in Africa in the year 2010 to provide the information that could assist health policy in the region. Methods: We conducted a systematic review of Medline, EMBASE and Global Health for studies on COPD published between 1990 and 2012. We included original population based studies providing estimates of the prevalence of COPD. We considered the reported estimates in terms of the mean age of the sample, sex ratio, the year of study and the country of the study as possible covariates. Results from two different types of studies, i.e., based on spirometric and non-spirometric diagnosis of COPD, were further compared. The United Nation Population Division's population figures were used to estimate the number of COPD cases in the year 2010. Results: Our search returned 243 studies, from which only 13 met our selection criteria and only five were based on spirometry. The difference in the median prevalence of COPD in persons aged 40 years or older based on spirometry data (13.4%; IQR: 9.4%–22.1%) and non-spirometry data (4.0%; IQR: 2.1%–8.9%) was statistically significant ( p = 0.001). There was no significant effect of the gender or the year of the study on the reported prevalence of COPD in either set of studies. The prevalence of COPD increased with age in spirometry-based studies ( p = 0.017), which is a plausible finding suggesting internal consistency of spirometry-based estimates, while this trend was not observed in studies using other case definitions. When applied to the appropriate age group (40 years or more), which accounted for 196.4 million people in Africa in 2010, the estimated prevalence translates into 26.3 million (18.5–43.4 million) cases of COPD. Comparable figures for the year 2000 based on the same prevalence rates would amount to 20.0 million (14.1–33.1), suggesting an increase of 31.5% over a decade that is attributable to ageing of the African population alone. Conclusion: Our findings suggest that COPD is likely to already represent a very large public health problem in Africa. Moreover, rapidly ageing African population should expect a steady increase in the number of COPD cases in the next decade and beyond. The quantity and quality of available evidence does not match the size of the problem. There is a need for more research on COPD prevalence, but also incidence, mortality and risk factors in Africa. We hope this study will raise awareness of COPD in Africa and encourage further research.